Atividades experimentais na educação do campo: uma abordagem da aprendizagem significativa na escola Frei Carmelo, ramal do Cataiandeua - BRITO, Ana Cristina Muniz de (2019)
With the objective of studying the relevance of experimentation in science teaching, from the point of view of meaningful learning, a theory developed by David Ausubel, the present study emphasizes that the student, because he is selective, is not interested in activities that do not attract attention. influence in the teaching and learning process. Therefore, the relevance of the work is to consider that through the experiments in science classes the student begins to consider this discipline from another perspective, which provides a meaning in his study. In order to reach this proposal, the methodology of qualitative characteristic was adopted, which through bibliographic researches, consultations to academic papers related to the theme and application of questionnaires addressed to the teachers of natural sciences, served as reference for the development of the study. The locus of the research was Frei Carmelo elementary school, located in Cataiandeua, a rural community in the municipality of Abaetetuba. In this way, it was possible to verify that the experimentation should present, in its procedure, a sense for the students, that is to pass through the knowledge that the student already presents in order to be successful in the process of teaching and learning.